The Drosophila TNF receptor Grindelwald couples loss of cell polarity and neoplastic growth - Andersen, Ditte S.; Colombani, Julien; Palmerini, Valentina; Chakrabandhu, Krittalak; Boone, Emilie; Röthlisberger, Michael; Toggweiler, Janine; Basler, Konrad; Mapelli, Marina; Hueber, Anne-Odile; Léopold, Pierre (Nature (London), 2015)
Cell polarity is an important feature of many tissues and is often disrupted in cancer; the TNF receptor Grindelwald is now shown to have an important role in coordinating cell polarity and neoplastic growth in a Drosophila model. Linking cell polarity and neoplasia Cell polarity is an important feature of many tissues, and is often disrupted in cancer. This study demonstrates, in a Drosophila model, that the tumour necrosis factor receptor molecule Grindelwald plays an important role in coordinating cell polarity and neoplastic growth. The authors identify Grindelwald as the long-sought receptor for the apoptosis-inducing factor Eiger, and show that Grindelwald functions by integrating signals from Eiger as well as from cell polarity cues. Disruption of epithelial polarity is a key event in the acquisition of neoplastic growth. JNK signalling is known to play an important part in driving the malignant progression of many epithelial tumours, although the link between loss of polarity and JNK signalling remains elusive. In a Drosophila genome-wide genetic screen designed to identify molecules implicated in neoplastic growth 1 , we identified grindelwald ( grnd ), a gene encoding a transmembrane protein with homology to members of the tumour necrosis factor receptor (TNFR) superfamily. Here we show that Grnd mediates the pro-apoptotic functions of Eiger (Egr), the unique Drosophila TNF, and that overexpression of an active form of Grnd lacking the extracellular domain is sufficient to activate JNK signalling in vivo . Grnd also promotes the invasiveness of Ras V12 /scrib −/− tumours through Egr-dependent Matrix metalloprotease-1 (Mmp1) expression. Grnd localizes to the subapical membrane domain with the cell polarity determinant Crumbs (Crb) and couples Crb-induced loss of polarity with JNK activation and neoplastic growth through physical interaction with Veli (also known as Lin-7). Therefore, Grnd represents the first example of a TNFR that integrates signals from both Egr and apical polarity determinants to induce JNK-dependent cell death or tumour growth.